Pegaruh Kepercayaan Konsumen Terhadap Keputusan Pembelian di Tokopedia Melalui Electronic Word of Mouth Sebagai Variabel Intervening - Andre Wijaya; Adryan Rachman (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
With rapid growth, researchers are intrigued to investigate the factors influencing consumer purchasing decisions on this platform. Through data collection and analysis, this research aims to provide deeper insights into how electronic word of mouth (e-WOM) influences purchasing decisions on Tokopedia. As a popular e-commerce platform, further understanding of these factors is expected to contribute to the development of marketing strategies and enhancement of consumer experiences on Tokopedia. This study utilizes purposive sampling and non-probability sampling techniques, involving 200 respondents from the community of Tangerang City who use Tokopedia for daily shopping. Data collection is carried out through G-form tools and manual methods with a questionnaire of statements using a 5-point Likert scale. The research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) techniques for hypothesis testing and data validity. From the discussion of each hypothesis, some hypotheses are rejected as they surpass the theoretical significance value. The variable rejected is the consumer trust variable in purchasing decisions. This rejection aligns with prior research on Scarlett products, finding that consumer trust has a positive and significant impact on purchasing decisions, while brand image and brand ambassadors do not significantly influence purchasing decisions (Putri & Harti, 2022). The results of this study indicate that the role of electronic word of mouth (e-WOM) mediates the influence of consumer trust on purchasing decisions among Tokopedia users in Tangerang City.